The culture of time and space 1880-1918 - Kern, Stephen (Harvard University Press, 1998)
Stephen Kern writes about the sweeping changes in technology and culture between 1880 and World War I that created new modes of understanding and experiencing time and space. To mark the book’s twentieth anniversary, Kern provides an illuminating new preface about the breakthrough in interpretive approach that has made this a seminal work in interdisciplinary studies.